2009
DOI: 10.1007/s10238-008-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol dehydrogenase isoenzymes and aldehyde dehydrogenase activity in the sera of patients with esophageal cancer

Abstract: Various alcohol dehydrogenase (ADH) isoenzymes and aldehyde dehydrogenase (ALDH) exist in the human esophageal mucosa. In our last experiments we have shown that ADH and ALDH are present also in the esophageal cancer cells. Moreover, the activities of total ADH and class IV isoenzymes were significantly higher in cancer tissue than in healthy mucosa, which suggests that these changes may be reflected by enzyme activity in the serum. Therefore, we measured the activity of total alcohol dehydrogenase, and classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In our previous study we found that the total alcohol dehydrogenase activity was changed in the serum of patients with esophageal cancer. The increase intotal ADH activity was positively correlated with ADH IV implicating that the latter isoenzyme was mainly responsible for the increase of total serum alcohol dehydrogenase activity in the course of esophageal cancer (Jelski et al, 2009b). The present study is a continuation of our previous research.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our previous study we found that the total alcohol dehydrogenase activity was changed in the serum of patients with esophageal cancer. The increase intotal ADH activity was positively correlated with ADH IV implicating that the latter isoenzyme was mainly responsible for the increase of total serum alcohol dehydrogenase activity in the course of esophageal cancer (Jelski et al, 2009b). The present study is a continuation of our previous research.…”
Section: Discussionsupporting
confidence: 79%
“…The total ADH activity has been elevated in the sera of patients with esophageal cancer. The increase in total ADH activity was positively correlated with class IV ADH and seems to be caused by the release of this isoenzyme from the cancer tissue (Jelski et al, 2009b).…”
Section: Introductionmentioning
confidence: 87%
“…Both the serum and tissue expression level of class I and total ADH were significantly increased in liver,27,28 colorectal,29,30 and brain cancers,31,32 while ALDH levels were not statistically significant different between cancer patients and healthy subjects. The upregulation trend of class I ADH between cancer and healthy tissue can also be found in cervical,33 ovarian,34 endometrial,35 and renal cell cancers,36 whereas the upregulation trend of class I ADH for cancer serum has been reported in bladder and esophageal cancers 37,38. However, the expression of class I ADH in breast cancer was significantly decreased compared to the tissue of healthy subjects, and the expression of ALDH was unchanged 39.…”
Section: Discussionmentioning
confidence: 95%
“…Various studies have pointed out that an imbalance between the activities of ADH and ALDH play a critical role in alcoholinduced neoplasm [33]. Essentially higher actions of different isoforms have been stated in esophageal cancer [34], liver cancer [35], and cervical cancer [36]. Acetaldehyde may be the significant cancer-causing agent in the upper and lower gastrointestinal tract, as acetaldehyde concentrations in saliva and in the large intestine are enough to facilitate in it and act as a carcinogen [37][38][39][40][41][42].…”
Section: Common Mechanism Of Carcinogenicity In Alcoholmentioning
confidence: 99%